Solution-processable two-dimensional ultrathin nanosheets induced by self-assembling geometrically-matched alkane. (June 2020) - Luo, Dan; Zhou, Boyang; Guo, Bowen; Gao, Peng; Zheng, Lei; Zhang, Xiaojun; Cui, Shengjie; Zhou, Hongjun; Zhou, Yongsheng; Liu, Yan
Abstract: Two-dimensional (2D) nanomaterials have attracted much interest as promising candidates for next generation energy storage, electronics and catalytic applications, due to their unique topology and electronic structure. However, the development of an operable and versatile solution processing technique for simple fabrication of high-quality 2D nanosheets continues to present a significant challenge. Here, an ultrathin indium sulfide nanosheet is synthesized via a simple solution-phase reaction involving two steps: i) thermal decomposition of precursors to form a crystal nucleus; ii) growth of 2D nanosheets in a mixture of amino ligand and alkane solvent. The alkane, matching the amino ligand structure in terms of geometry, could assemble with the ligand to form a soft template and thus induce a 2D arrangement of the nucleus. Moreover, the chemical inertness of the alkane facilitated rotation of crystal seeds, resulting in anisotropic growth of the nanosheet. We further demonstrated that the geometrically matched alkane-assisted solution processing reaction could be applied to synthesize various 2D metal chalcogenides. Functionally, the acquired indium sulfide nanosheets, which possess high photoelectric activity, were introduced for fabrication of photoelectrodes capable of efficient photoelectrochemical water splitting. Our work opens up a new perspective toward the construction and potential applications for various 2D nanomaterials. Graphical abstract: A geometrically matched alkane-assisted solution processing strategy has been developed to synthesize In2 S3 and other metal chalcogenide nanosheets. The integrated self-assembly of amino ligands and alkane solvent molecules forms a soft template, guiding the anisotropic growth of nanosheets. The chemical inertness and stoichiometry of the alkane determines the nanotopography of the materials. The acquired In2 S3 nanosheets are introduced for fabrication of photoelectrodes capable of efficient photoelectrochemical water splitting. Image 1 Highlights: Developing a simple and versatile solution processing strategy for fabricating metal chalcogenide ultrathin nanosheets. In-depth insight into the fine structures and photoelectric activity of In2 S3 ultrathin nanosheets. Construction of composite photoelectrodes for efficient photoelectrochemical water splitting.